Thermoregulation in the Brain and Body: Understanding the Influence of Memory on Innate Responses - Marks, Lydia Corbin (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2021)
Thermoregulation is the ability for an organism to maintain a specific internal temperature while existing in an environment with constantly changing external temperatures. This is a critical homeostatic response and the inability to thermoregulate can be life-threatening. Therefore, understanding the thermoregulatory system within mammals has been pertinent to biological research for centuries. The brain plays a crucial role in sensing temperature changes and initiating the appropriate thermoregulatory responses. Recent technological developments have enabled the investigation of neuronal mechanisms driving innate thermoregulatory responses. This project aims to further our understanding of the components influencing thermoregulation. Engram labelling technology, originally used in memory research, will be optimised to label and manipulate the specific temperature-sensitive neurons within the brain. This research will also investigate whether innate thermoregulatory responses can be modulated by learning and memory. The aim is to further our understanding of the relationship between learned and innate responses.
APPROVED
Keywords: engram labelling; thermoregulation; hypothalamus